Defect Chemistry in Discharge Products of Li–O2 Batteries. Issue 3 (19th November 2018) - Dai, Wenrui; Cui, Xinhang; Zhou, Yin; Zhao, Yong; Wang, Li; Peng, Luming; Chen, Wei
Abstract: Li–O2 batteries, possessing the highest theoretical specific energy density among all known Li‐ion‐based batteries, demonstrate great potential as energy storage devices for powering electric vehicles. However, their battery performance is significantly limited by the insulating nature of the discharge product Li2 O2, which has a wide bandgap (4–5 eV), resulting in high charge overpotential. Defect engineering of the discharge product emerges as a very promising strategy to improve the electrical conductivity and hence reduce the charge overpotential. The aim of this review is to highlight recent advances and progress in understanding and controlling the defect chemistry of discharge products in Li–O2 batteries. First, the theoretical perspectives of defects in Li2 O2 are reviewed, with particular emphasis on defect design and engineering strategies to significantly improve the charge transport properties of Li2 O2 . Then intermediate defects in Li2 O2 formed during the discharge and charge processes and materials with induced defects, including Li2− x O2, doped Li2 O2, Li2 O2 with surface/grain boundaries, and amorphous Li2 O2, which are tailored by engineered catalysts and electrolyte additives are discussed. Finally, other alternative energy carriers for new energy storage chemistry of Li–O2 batteries, such as lithium superoxide, lithium hydroxide, and lithium carbonate, will also be discussed. Abstract : Defect engineering of Li2 O2 emerges as a promising strategy to improve Li–O2 battery performance. The recent progress and advancements in the defect chemistry of Li2 O2, including Li‐deficient Li2 O2, doped Li2 O2, Li2 O2 with surface/grain boundaries, and amorphous Li2 O2, are reviewed. The implications of other energy carriers (e.g., LiO2, LiOH, Li2 CO3 ) on Li–O2 battery performance are also presented.